2019
DOI: 10.14311/cej.2019.02.0016
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis About Blasting Effect of Digital Detonator and Millisecond Detonator in Upper and Lower Cross Tunnels

Abstract: In order to study on the vibration effect of the blasting in the upper and lower cross tunnels, depress the impact of blasting vibration on existing adjacent tunnel and acquire the sound way of tunnel blasting construction, the finite element software LS-DYNA was adopted to calculate what vibration effect of existing tunnel would be generated by the different detonation modes (simultaneous initiation and hole-by-hole initiation) and the different cut modes (parallel cut and oblique cut). In general, the result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Previous studies have shown that the superposition and attenuation of stress waves for porous blasting are related to both the time difference of detonation and the physical property of the surrounding rock [12]. With the development and application of digital electronic detonator technology [24,25], it is possible to reduce the blasting vibration velocity by the time difference of detonation on the basis of the superposition principle of blasting stress waves. Subject to the complexity of the actual working conditions, the amount of experimental and theoretical research conducted in this area is very limited; especially in a new tunnel excavation adjacent railway tunnel, the construction standard is extremely strict and the specification cannot be unified.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the superposition and attenuation of stress waves for porous blasting are related to both the time difference of detonation and the physical property of the surrounding rock [12]. With the development and application of digital electronic detonator technology [24,25], it is possible to reduce the blasting vibration velocity by the time difference of detonation on the basis of the superposition principle of blasting stress waves. Subject to the complexity of the actual working conditions, the amount of experimental and theoretical research conducted in this area is very limited; especially in a new tunnel excavation adjacent railway tunnel, the construction standard is extremely strict and the specification cannot be unified.…”
Section: Introductionmentioning
confidence: 99%